(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The section of this study where we discuss the complaints is very informative. Complaints are a normal part of life, and we struggle with numerous issues everywhere. The barangay desk officer stated that their role is to handle both parties’ complaints so that both parties can understand when an agreement has been reached that would satisfy both parties where discussion can take place at the barangay office desk the neighborhood is assured by us Desk officers are well trained on how to deal with complainants’ complaints.